Optimalisasi Program Pelayanan Sosial untuk Remaja: Studi pada Dinas Sosial PPPA Kabupaten Nganjuk - Kamila Sholekah; Vidya Imanuari Pertiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Teenagers who drop out of school or are neglected are a social problem whose impact can be felt by the individuals themselves and also society. In an effort to reduce teenagers who drop out of school or are neglected, cooperation from various government and private parties is needed. One of them is a social service program which aims to ensure that they continue to receive education outside of school and receive guidance. One way to respond to this is that the Indonesian government has made strategic efforts through the Ministry of Social Affairs of the Republic of Indonesia to establish a social welfare management program for social services throughout Indonesia, especially in East Java social services by forming a UPT which has a coaching program for teenagers who have dropped out of school. namely UPT PSBR. The background of this research is to describe the effectiveness of the youth development social service program which is a program of the East Java Provincial Social Service down to the UPT PSBR and followed by the Nganjuk Regency PPPA Social Service in dealing with teenagers who have dropped out of school. Seeing how the PPPA Social Service in Nganjuk district handles and empowers children who are neglected or have dropped out of school through this program. This type of research is qualitative. This research aims to describe the condition of facts in the field using analysis based on certain data (information). There are 3 methods used for data collection, namely interviews, documentation and field observations. The results of this research show that this program is beneficial and effective for teenagers who have dropped out of school as evidenced by the accuracy of targeting in selecting participants, achieving the set goals, monitoring the program which is beneficial for graduates assisted by PSBR. However, there are still other problems such as the public's lack of knowledge about the PSBR program, this is because the socialization is still carried out using simple methods.